Effect of Low-Frequency rTMS and Intensive Speech Therapy Treatment on Patients With Nonfluent Aphasia After Stroke. Issue 1 (January 2021) - Bai, Guangtao; Jiang, Liang; Ma, Wenshuai; Meng, Pingping; Li, Jiang; Wang, Yuyang; Wang, Qiang
Abstract : Background: To observe the effect of low-frequency repetitive transcranial magnetic stimulation (rTMS) on patients with nonfluent aphasia after stroke. Materials and Methods: Thirty patients were divided into control, rTMS, and 2 times a day low-frequency rTMS (2rTMS) groups, and all 3 groups had intensive speech therapy (ST). Patients were assessed by western aphasia battery (WAB) scale. The spontaneous language, listening comprehension, retelling, and naming were scored, respectively. The expression of brain-derived neurotrophic factor (BDNF) in peripheral blood was detected by enzyme-linked immunosorbent assay. Results: There was significant difference in aphasia quotient after treatment in the 3 groups. The values of the 4 dimensions in the WAB score of the rTMS group were higher than those in the control group. The WAB scores in the 2rTMS group were higher than those in the rTMS group. After 2 weeks treatment, the BDNF levels in the rTMS group and the 2rTMS group were significantly higher than those in the control group. Four weeks later, the 2rTMS group was significantly increased compared with the control group and the rTMS group. Conclusions: Low-frequency rTMS combined with conventional ST treatment can effectively improve the language function of patients with nonfluent aphasia after stroke. Two times a day low-frequency rTMS therapy combined with conventional ST treatment can improve the language function of patients with nonfluent aphasia after stroke more effectively and it also promote the expression of BDNF more effectively, thereby improving nerve repair and protecting brain tissue.